The impact of combination of core stabilization exercise and walking on pain perception and low-back pain disability - Fariba Hossein Abadi; Nur Halimatulsa'adiah A. Tiis; Fairus F. Zainuddin; Wallapa Choeibuakaew; Gunathevan Elumalai; Mohansundar Sankaravel; Saeid Motevalli (IP Iermakov S.S., 2022)
Background and Study Aim. Low-back pain (LBP) has increasingly been the leading cause affecting work performance, daily activities, and rising the cost of healthcare services. Currently, sitting time increases and walking activity lessens among people. The purpose of this study - identify the effect of Core Stabilization Exercise (CSE) with walking on pain perception and LBP disability among people who suffered from non-specific low-back pain (NSLBP). Material and Methods. In this study, a total of 36 active people (18-42 years old) with BMI≥24.9 kg.m-2 voluntarily participated and were divided randomly into three groups. Intervention groups included CSE group (CSEG; n=12), CSE with walking (CSEWG; n=12), and control group (CG; n=12). The intervention groups carried out the exercise programs (CSE with and without 30 minutes of walking), three times a week for six weeks. In this study, the pain perception was assessed via the Numerical Pain Rating Scale (NPRS) and LBP disability was measured by using a modified Oswestry Disability (ODI) questionnaire. Results. A one-way analysis of variance (ANOVA) displayed significant effectiveness of CSEG and CSEWG on pain perception as the interaction between time and group [f (2, 33) = 4.95, p=0.032]. The pain perception significantly decreased in CSEG (p=0.021) and CSEWG (p=0.003) after six weeks of the intervention programs compare to CG. The results also showed a significant effect on LBP disability for the interaction between time and group after six weeks of both intervention programs (f (2, 33) =6.52, p=0.015). Disability function (ODI score) significantly improved in CSEG (p=0.031) and CSEWG (p=0.007). Even though the results revealed no significant difference between CSEG and CSEWG, and both groups proved to reduce pain perception and LBP disability, the disability index improvement was greatest in CSEWG. Conclusions. In conclusion, CSE with 30 minutes of walking, as an intervention program, has shown greater improvement with a larger effect size in pain perception and LBP disability among people who suffered from NSLBP.